L'engagement des enseignants dans un dispositif d'enseignement à distance - Jean-Michel Gélis (Centre National d'Enseignement à Distance, 2013)
The department of pre-service teacher education of the Cergy Pontoise university decided in 2010 to organize an e-learning version of its courses. In order to go as fast as possible, teachers of the department were all of them volunteers. In this paper, we focus on a team of mathematics teachers whose discourses were recorded at the end of their first year of practice. We precise adaptations teachers have made to perform their synchronic interactions, to deal with particular students and courses learning. We also stress their limits, about problems situations design and about collaborative and socio-constructivist aspects. We refer to theoretical frameworks originating from educational sciences and didactics of mathematics. A final discussion allows us to point out some consequences and take a more general point of view.